2011
DOI: 10.3340/jkns.2011.50.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Brainstem Metastasis

Abstract: small case series for the management of brainstem metastases using Gamma Knife Radiosurgery (GKRS) 12,16,18,22,26,35) . The present study assessed outcomes following our use of GKRS for the management of brainstem metastasis, and we investigated the effect of treatment on tumor size and survival time. MATERIALS AND METHODS Patient characteristicsFrom November 1992 to June 2010, a total of 32 patients underwent GKRS for local control of brainstem metastasis at our institute. The clinical characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Smalley et al (13) reported a median survival time of 11.7 months following resection of solitary brain metastases. Generally, brainstem metastases are not treated with conventional neurosurgery due to the risk of neurological damage (9,10), and Gamma Knife surgery is typically considered for brainstem metastasis (9) Gamma knife surgery exhibits a local control rate of 83-94% with a median survival time of 7-12 months (10). In the present case, gamma knife surgery may have been an appropriate treatment for tumor control.…”
Section: Discussionmentioning
confidence: 93%
“…Smalley et al (13) reported a median survival time of 11.7 months following resection of solitary brain metastases. Generally, brainstem metastases are not treated with conventional neurosurgery due to the risk of neurological damage (9,10), and Gamma Knife surgery is typically considered for brainstem metastasis (9) Gamma knife surgery exhibits a local control rate of 83-94% with a median survival time of 7-12 months (10). In the present case, gamma knife surgery may have been an appropriate treatment for tumor control.…”
Section: Discussionmentioning
confidence: 93%
“…During 1999-2013, nine patients' series [4,[6][7][8][10][11][12][13][14] with brainstem metastases treated with SRS (GKRS) were reported. The samples of these studies varied between 25-200 patients and the number of irradiated lesions ranged from 26 to 222 tumors.…”
Section: Patients' Seriesmentioning
confidence: 99%
“…Its management includes standard radiation and chemotherapy, while surgical resection is not a routine procedure due to its high risks. [4,6,7] For these patients SRS (GKRS) is nowadays used as a feasible treatment option and is considered as a treatment modality expected to achieve a radical cure. [7,8] Furthermore, GKRS is an effective therapy (a non-invasive alternative to surgery) for primary brainstem tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations